2015
DOI: 10.1016/j.clinbiochem.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Use of biomarkers for the assessment of chemotherapy-induced cardiac toxicity

Abstract: Objectives To review the evidence for the use of various biomarkers in the detection of chemotherapy associated cardiac damage. Design and methods Pubmed.gov was queried using the search words chemotherapy and cardiac biomarkers with the filters of past 10 years, humans, and English language. An emphasis was placed on obtaining primary research articles looking at the utility of biomarkers for the detection of chemotherapy-mediated cardiac injury. Results Biomarkers may help identify patients undergoing tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 157 publications
(196 reference statements)
1
101
0
3
Order By: Relevance
“…In 2004, the FDA concluded that TnI is a sensitive, specific and robust biomarker for cardiac damage, allowing the detection and quantification of cellular damage and death [8]. TnI levels have been shown to increase progressively after more AC doses, being associated with a significantly higher risk of left ventricular dysfunction [5]. Given the low elevations of troponin levels that occur after doxorubicin administration, some studies believe that they may represent physiologic variations [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004, the FDA concluded that TnI is a sensitive, specific and robust biomarker for cardiac damage, allowing the detection and quantification of cellular damage and death [8]. TnI levels have been shown to increase progressively after more AC doses, being associated with a significantly higher risk of left ventricular dysfunction [5]. Given the low elevations of troponin levels that occur after doxorubicin administration, some studies believe that they may represent physiologic variations [8].…”
Section: Discussionmentioning
confidence: 99%
“…AC-induced cardiac injury is dose dependent and the international recommendations are not to exceed 450-550 mg/mÂČ [3], although even lower doses have led to cardiac damage in certain patients [4]. The gold standard for cardiotoxicity detection is serial echocardiography, used prior to treatment initiation and during the course of chemotherapy [5]. Cardiac biomarkers (troponin T, troponin I (TnI), natriuretic peptides, high-sensitivity C reactive protein, glycogen phosphorylase isoenzyme BB, heart-type fatty acid binding protein (H-FABP), myeloperoxidase, total antioxidant status, circulating microRNAs, creatinine kinase) represent an attractive alternative for the detection of cardiotoxicity and are intensively analysed for many advantages such as being operator-independent, non-invasive and a resource-efficient approach [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that both troponin I and T may detect cardiotoxicity long before any reduction in LVEF has occurred in patients treated with different chemotherapy schedules, containing old and new antitumor drugs [16][17][18]. Additional uses for troponins in patients undergoing anticancer therapy include the following:…”
Section: Troponinsmentioning
confidence: 99%
“…Accumulating evidences indicate that DOX-induced cardiac dysfunction is caused by the perturbation of several physiological pathways, particularly the DNA-damage response pathway [4]. Unfortunately, many of the mechanisms at the base of this phenomenon are not clearly understood yet, and no reliable early toxicity biomarkers are available [5,6]. Cardiac dysfunction insurgence can be assessed by mean of different approaches: angiography, LVEF evaluation by echocardiography, and endomyocardial biopsy.…”
Section: Cardiotoxicity Markersmentioning
confidence: 99%
“…The most reliable early marker for detection of heart damage is represented by cardiac troponins, which are routinely used as circulating indicators of cardiac necrosis, a condition characterizing (among other pathologies) myocardial infarction and myocarditis [5,7]. Other possible biomarkers such as tumor necrosis factor α (TNF-α), galectin-3, IL-6, ST2 and sFlt-1 have been evaluated in order to detect subclinical cardiotoxicity after treatment with anthracyclines, but they did not show any clinical value [8].…”
Section: Cardiotoxicity Markersmentioning
confidence: 99%